2010
DOI: 10.7763/ijtef.2010.v1.32
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Tourism Development in Protected Areas. A Case of Kinabalu Park

Abstract: Abstract-Sustainable tourism emerges as more responsible form of tourism seeks to minimize the undesirable impacts of tourism development at destination level. Specifically, its presence in nature-based tourism destinations provides financial revenue for nature conservation through maintaining high quality visitor experience. Kinabalu Park is the first World Heritage Site of Malaysia. Since its establishment in 1964, the park has been a popular tourism destination in the country and in the region. The signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…Poring Hot Spring stood at an altitude of 500m above sea level thus having an average temperature around 25-30 o C. The temperature at Panar Laban/Laban Rata at 3,344m above sea level is recorded between 2-10°c and can drop below freezing point during the nights. The average annual rainfall in Park HQ is recorded at 4,000mm while in Poring Hot Spring, at 2,500mm (Goh [15]). …”
Section: Kinabalu Park At a Glancementioning
confidence: 99%
See 2 more Smart Citations
“…Poring Hot Spring stood at an altitude of 500m above sea level thus having an average temperature around 25-30 o C. The temperature at Panar Laban/Laban Rata at 3,344m above sea level is recorded between 2-10°c and can drop below freezing point during the nights. The average annual rainfall in Park HQ is recorded at 4,000mm while in Poring Hot Spring, at 2,500mm (Goh [15]). …”
Section: Kinabalu Park At a Glancementioning
confidence: 99%
“…The average temperature in Kinabalu Park differs between substations. At an elevation of 1,560m above sea level, the daily temperature at Park HQ is around 20 o C. At Mesilau Nature Resort, the temperature is slightly lower than at Park HQ, at [15][16][17][18] o C due to the higher altitude (2,000m above sea level). Poring Hot Spring stood at an altitude of 500m above sea level thus having an average temperature around 25-30 o C. The temperature at Panar Laban/Laban Rata at 3,344m above sea level is recorded between 2-10°c and can drop below freezing point during the nights.…”
Section: Kinabalu Park At a Glancementioning
confidence: 99%
See 1 more Smart Citation
“…Her work is closely related to the findings of Goh who undertook a detailed study of Kinabalu National Park and concluded that 'the privatization program has not been able to shift the focus of Sabah Parks to nature conservation and that the private sector is unable to fulfil all objectives of sustainable tourism ' (2007, p. iii;and see Zeppel 2006). She examined sustainability from three perspectives: environmental conservation and protection; benefits to local communities; and visitor satisfaction (Goh 2007, p. 124;and see Goh 2009;Goh and Masiney 2010;Goh and Rosilawati 2014). An informative context for this case study in Sabah is provided by Pianzin's examination, though now somewhat dated, of the management of tourism development in Sabah (1992).…”
Section: Nature Ecotourism Imaging and Sustainabilitymentioning
confidence: 99%
“…Kinabalu National Park is a protected area under category II identified by the International Union for Conservation of Nature (2000); it has also been declared by the United Nations Educational, Scientific, and Cultural Organization World Heritage Committee (UNESCO WHC, 2013) as a World Natural Heritage Site. Privatization has been implemented in Kinabalu Park since 1998, but it is still managed by a local authority, namely, Sabah Parks (Goh & Yusoff, 2010). However, the role of a tour operator cannot be neglected, because Kinabalu Park is one of the main destinations packaged by tour operators and sold to tourists.…”
Section: Introductionmentioning
confidence: 99%